English learning system using speech recognition for visual impaired user (ELSRVI) - Rajinder Singh, Harvinder Kaur (2012)
English Learning System Using Speech Recognition for Visual Impaired User (ELSRVI) is a prototype which is embedded with speech recognition and aimed at Visual impaired user that have the speaking and hearing ability.This system is user friendly since user do not need to navigate the computer by using normal keyboard.Besides that,this system is also created to fulfill all the objectives of the system.The objectives are to develop a prototype to determine English learning system using speech recognition engine for visual impaired user to get accessed to computer through speech and to identify the suitable techniques and software to create the English learning system using speech recognition engine for visual impaired user.So,the interaction between humans and computers will be more natural if computers are able to understand the speech and recognize it.The technique that will be used is in develop the system is Linear Predictive Coding (LPC).The methodology use is Rapid application Development (RAD).This system is also create'd due to improvement in the new technologies nowadays which is more enhanced and mainly to overcome the problem faced by visual impaired user in their education life.Finally,in this report will discuss on the preparation and analysis that have been done in order to develop this system.A complete reference and research details have been inserted in this document.This document will be a quick reference to refer on the specification and requirements of the system.